Definitional differences in “outpatient” surgery can influence study outcomes related to total shoulder arthroplasty - Junho Song, MD; Jennifer Yu, BS; Avanish Yendluri, BS; William A. Ranson, MD; Nikan K. Namiri, MD; John J. Corvi, MD; David E. Kantrowitz, MD; Thomas Boucher, MD; Leesa M. Galatz, MD; Paul J. Cagle, MD; Bradford O. Parsons, MD; Robert L. Parisien, MD (JSES International)
Background: Numerous studies have investigated the outcomes of outpatient total shoulder arthroplasty (TSA). However, some patients originally planned for outpatient surgery may unexpectedly require inpatient hospital stay, which can obscure the distinction of “outpatient” and “inpatient” cases. Ultimately, this inconsistent classification of “outpatient” surgery may influence study results. The objectives of this study were (1) to characterize the differences in definition of “outpatient” surgery (hospital-defined outpatient [HDO] vs. same-day discharge [SDD]), and (2) to study the effect of different definitions on 30-day outcomes following TSA. Methods: The American College of Surgeons National Surgical Quality Improvement Program database was queried for patients who underwent TSA between 2011 and 2021. HDO cases were identified based on the National Surgical Quality Improvement Program inpatient or outpatient variable, and SDD cases were identified based on length of stay = 0. Demographic and clinical characteristics were compared between HDO and SDD cohorts. Propensity score was utilized to match each HDO and SDD case with one inpatient case without replacement. Two distinct sets of multivariate analyses, using Poisson regressions with robust error variance, were performed to calculate the risks of readmission, reoperation, morbidity, and complications for HDO and SDD. Results: A total of 30,458 patients met the inclusion criteria, including 6711 HDO and 4490 SDD cases. 3501 out of the 6711 (52.2%) HDO patients required at least one night of inpatient hospital stay (length of stay >0). Between 2011 and 2021, the annual incidence of HDO TSA rose from 4.1% to 61.6% of all TSA cases, and the incidence of SDD TSA increased from 2.0% to 34.1% of all TSA cases. Compared to SDD, HDO was associated with female sex, higher body mass index, functional dependence, diabetes, chronic obstructive pulmonary disease, congestive heart failure, hypertension, American Society of Anesthesiologists ≥3, longer operation time, and nonhome discharge. After controlling for potential confounders, inpatient TSA was associated with increased risk of 30-day readmission and reoperation compared with HDO cases, while morbidity and individual complication rates were similar. However, compared with SDD patients, inpatient TSA was associated with higher rates of readmission, reoperation, morbidity, pneumonia, pulmonary embolism, myocardial infarction, and deep venous thrombosis. Conclusion: Definitional differences in “outpatient” surgery can lead to significantly different study outcomes related to TSA. Future investigations on this topic should maintain consistency in the definition of “outpatient” surgery. Accurate data on the risk factors for adverse events after TSA are critical for appropriate patient selection and improving surgical outcomes.